FACTOR ANALYSIS ON EMPLOYEE RETENTION AT IBIS HOTEL MANADO - Mamahit, Nikita Isabella; Worang, Frederik G.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Human Resource Management is very important in hospitality industry. One of this hospitality industry that operates in manado city is Ibis hotel. In this hotel, it’s important to discuss about employee retention. Employee retention means keeping right people on right jobs for every organization. This research aims to analyze the problem about employee retention in Ibis hotel Manado. This study aims to define the factors that affecting employee retention in Ibis Hotel Manado and to determine which factors most impacting employee retention in Ibis Hotel Manado. This research utilizes descriptive quantitative method. Populations and samples in this study are the employees of Ibis Hotel Manado, using saturated sampling technique in collecting sample research from respondents. The results of this research conclude that there are four factors that impacts the employee retention of Ibis Hotel Manado, such as talent management factor, consisted of training and development, perceived of organizational support, organizational justice, job autonomy, career development, commitment, performance appraisal and employee empowerment variable. Workload factor, consisted of by job satisfaction, work environment, leadership, organizational culture, and work life balance social interaction factor, consisted of demographics, mentoring and compensation variable. Psychological well-being factor, consisted of reward, job stress, and job security variable.Keywords: employee retention, factor analysis, talent management, workload, psychological well-being, job security.